The effects of motivational reward on the pathological attentional blink following right hemisphere stroke. (November 2016) - Li, Korina; Russell, Charlotte; Balaji, Nikita; Saleh, Youssuf; Soto, David; Malhotra, Paresh A.
Abstract: Recent work has shown that attentional deficits following stroke can be modulated by motivational stimulation, particularly anticipated monetary reward. Here we examined the effects of anticipated reward on the pathological attentional blink (AB), an index of temporal selective attention, which is prolonged in patients with right hemisphere damage and a history of left neglect. We specifically compared the effects of reward versus feedback-without-reward on the AB in 17 patients. We found that the patients all manifested impaired performance compared to healthy controls and that reward modulated the pathological blink in the patient group, but only in the second experimental session. When the performance of patients whose neglect had recovered was compared with that of patients who had ongoing or persistent neglect, reward appeared to only influence the AB in the former. These results have implications for our understanding of motivation-attention interactions following right hemisphere stroke, and how they may impact upon recovery from spatial neglect. Highlights: Anticipated reward can modulate the pathological attentional blink in right hemisphere stroke. Reward's effects are greater than those of performance feedback alone. Reward response appears to be related to neglect recovery.